2015
DOI: 10.3171/2014.9.peds14126
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic infarction following open fenestration of a large intracranial arachnoid cyst in a pediatric patient

Abstract: Intracranial arachnoid cysts are a rare condition thought to be congenital in nature. Treatment of intracranial arachnoid cysts remains controversial based on their variable presentation. Treatment options include CSF shunting, endoscopic fenestration, or craniotomy and open fenestration for larger cysts. The complications of these procedures can include hydrocephalus, subdural hematomas, hygromas, and—more rarely—intraparenchymal hemorrhage. The authors found very few reports of hemorrhagic infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The rate of complications and treatment failure associated with the surgical treatment of ACs is quite high [2,3,24], even in studies by those in favor of surgery based on broad indications [6]. Considering the benign nature and the scarce natural history of this condition in most cases, serious surgical complications, such as hemorrhage, infarction, meningitis, and neurological deficits, are hard to accept [1,2,25]. Despite our findings of good long-term functional outcomes, with no permanent morbidity after surgery, the objective improvement is often difficult to quantify and validate.…”
Section: Discussionmentioning
confidence: 96%
“…The rate of complications and treatment failure associated with the surgical treatment of ACs is quite high [2,3,24], even in studies by those in favor of surgery based on broad indications [6]. Considering the benign nature and the scarce natural history of this condition in most cases, serious surgical complications, such as hemorrhage, infarction, meningitis, and neurological deficits, are hard to accept [1,2,25]. Despite our findings of good long-term functional outcomes, with no permanent morbidity after surgery, the objective improvement is often difficult to quantify and validate.…”
Section: Discussionmentioning
confidence: 96%
“…In our literature review, only 1 case of such an occurrence was reported; the cause of the hematoma was reperfusion injury that occurred after reduction of the intracranial pressure and damage to the bridging vein caused by displacement of the cysts after their release. [ 17 ] In our case, the patient had clear symptoms, and the surgical indications were clear. However, this complication after surgery was serious and rare and should therefore be registered in the literature.…”
Section: Discussionmentioning
confidence: 54%
“…The complications of these procedures include subdural hematomas, hygromas, hydrocephalus, cerebral edema, postoperative secondary AC, and more rarely intraparenchymal or subarachnoidal hemorrhage. 6 We report large, unilateral MCF AC (Gallasi score III) linked with mild undefined symptoms and treated surgically via micro resection and fenestration of cyst walls followed by remote intraparenchymal and subarachnoid hemorrhage as an initial early postoperative complication.…”
Section: Introductionmentioning
confidence: 99%